Relationship between 24-hour blood pressure variability and mean carotid intimate index in essential hypertension - Suzana Maria Gubern; Nicoleta Avram; Cătălina Liliana Andrei; Crina Sinescu (Romanian Medical Journal, 2020)
Hypertension (HT) is recognized as a major risk factor for cardiovascular disease (CV) and mortality. The literature suggests that in order to achieve the highest degree of CV protection in hypertension, treatment should aim at decreasing the variability of blood pressure (BP) in 24 hours in addition to reducing the absolute levels of BP over 24 hours. Aim. The study purpose was to analyze the relationship between changes in BP values produced during the day, determined by ambulatory blood pressure measurement (ABPM) and target organs lesion expressed by the intima-media thickness of the carotid artery in a group of patients newly diagnosed with HT based on the hypothesis of correlation between systolic (s) and diastolic (d) BP variability and target organs lesion. Material and method. We enrolled 60 patients recently diagnosed with HT and not treated before enrollment. All subjects were monitored by ambulatory blood pressure monitoring and the degree of target organ lesion was assessed by carotidian intima-media thickness. BP variability was calculated as standard deviation (SD) and average real variability (ARV) of systolic and diastolic BP. The subjects were subsequently divided into quartiles of BP variability. The correlations between carotidian intima-media thickness and BP variability parameters, demographic parameters and hypertensive load were analised using Pearson coefficient. Results. The mean age of patients was 60.56 +/- 6.76 years, 43.33% were male, 66.66% had family history of HT. The mean body mass index (BMI) was 27.9 +/- 4.47 kg/m2. The analise of the quartiles of the BP variability parameters showed that the carotidian intima-media thickness value is not influenced by the average BP value and that the s BP variability calculated by DS is statistically significantly correlated with the carotidian intima-media thickness value. Using Pearson coefficient, we observed that the carotidian intimamedia thickness value is significantly correlated with the body mass index and with the variability of s BP expressed by both SD and AVR and with the variability of d BP expressed by SD. It was also observed that the hypertensive load is not correlated with the carotidian intima-media thickness value. The results of the present study showed that the variability of s BP/24 h is correlated with carotidian intimamedia thickness independent of mean BP values, in a cohort of recently diagnosed and untreated hypertensive subjects.